Association of serum lipid profile ratios with disease severity and in-hospital outcome of patients with COVID-19 - Azad, Md Abul Kalam; Areefin, Md Nafis; Murshed, Khaled Mahbub; Mahdi, Abdullah Al (BIRDEM Medical Journal, 2023)
Background: The association of lipid ratios with the severity and hospital outcome of COVID-19 patients has been a topic of interest in the medical community. Lipids, particularly cholesterol and triglycerides, play a significant role in the human body, including cell membrane formation, energy storage and the regulation of various biological processes. The aim of this study was to assess the association of lipid ratio with the severity and hospital outcome of COVID-19 patients. Methods: This observational study was carried out in COVID unit of Bangabandhu Sheikh Mujib Medical University (BSMMU) among hospital admitted COVID patients from March 2021 to February 2022. Results: Total patients were 138 including 65.9% males. Majority (27.5%) were in the 41-50 age group. One third (31.2%) were clinically severe COVID-19. There was overall significant difference of lipid ratio in different severity except LDL/HDL group (p>0.05). The correlation coefficients of disease severity with TC/HDL (rs)=.338, LDL/HDL (rs)=.289 and TG/HDL (rs)=.444. There was significant correlation between disease severity and lipid ratio having moderate correlation with TG/HDL and weak correlation with TC/HDL and LDL/HDL. The correlation coefficients between TC/HDL and hospital outcomes of use/development of rebreather (rs)=.217, HFNC (rs)=.282, ARDS (rs)=.307, arrhythmia (rs) = .201, HDU/ICU (rs)=.200 and ventilator (rs)=.072. There was significant correlation between TC/HDL and development of ARDS, use of rebreather and HFNC and no other significant correlation with other outcomes. The correlation coefficients between LDL/HDL and hospital outcomes of use/development of rebreather (rs)=.211, HFNC (rs)=.132, ARDS (rs)=.286, arrhythmia (rs)=.106, HDU/ICU (rs)=.064 and ventilator (rs)=.028. There was no significant correlation between LDL/HDL and hospital outcomes. The correlation coefficients between TG/HDL and hospital outcomes of use/development of rebreather (rs)=.427, HFNC (rs)=.271, ARDS (rs)=.502, arrhythmia (rs)=.088, HDU/ICU (rs)=.158 and ventilator (rs) =.041. There was significant correlation between TG/HDL and development of ARDS, also with use of rebreather and HFNC. No other significant correlation found with other outcomes. Conclusion: From the findings of this current study, in can be concluded that lipid ratios are associated with disease severity and hospital outcome of COVID-19 patients. There was moderate association between disease severity and TG/HDL and weak association with TC/HDL and LDL/HDL. There was also association between TC/HDL and the development of ARDS and the use of HFNC and between TG/HDL and the development of ARDS, the use of rebreather, and HFNC. BIRDEM Med J 2023; 13(2): 98-102